The impact of the learning organization and personal development on the personal perfromance of immigration department in Thailand: A pilot study for reliability and validity of instruments / Tunwarat Kongnun...[et al.] - Kongnun, Tunwarat; Kaewsom, Chumphon; Harun, Azhar; Yusof, Rohana (Universiti Teknologi MARA, Kedah, 2019)
The impact of the learning organization (LO) and personal development (PD) aims at contributing to the understanding to hope to improve the staff in the performance of the organization and researcher practice. Learning organization (LO) is one importance of the factor that influence performs to improve personal performance, including behavioral, cognitive performance, knowledge management, new flexible human resources and more adaptable organization designs. This study was to explore learning by organization member that contributes to their competence and effectiveness in their organization and how to develop the personal performance more effectively within the performance. This study examined the validity and the reliability of measurement instruments of the learning organization, personal development and that influence the personal performance of the immigration department in Thailand. The study employed survey approach in the collection of data via 30 usable questionnaires in the immigration department in Thailand. The validation and reliability of all constructs are determined for the acceptability of instruments using SPSS version 19, Cronbach’s Alpha indicated that all the items are valid and reliable in conducting the study